Students' Perception about the acquisition of abilities when concluding the subject Basic Cardiopulmonary Cerebral Resuscitation - José Julio Ojeda González; Olga Lidia Sánchez Sarría; Lino Ortiz Santiesteban; Pedro Nieto Prendes (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: Plan D of the Medical Major, among other things, has the task of achieving a graduate with abilities and competences according to their national and international performance. Aimed at this the subject Cardiopulmonary Resuscitation was included. Objective: to identify the student's perception about the basic abilities acquired when concluding the subject Basic Central Cardiopulmonary Resuscitation. Methods: exploratory study developed at the Medical University of Cienfuegos which included all the first year students of the Medical Major. A survey was applied in which the basic abilities to be achieved by the students after concluding the subject were listed. It was delivered during the first semester and in which this content was evaluated. Results: it was evident that most difficulties wer in controlling hemorrhage and basic vital support in trauma with 50 students self-evaluated of Insufficient (14,2 %), and 100 self-evaluated Fair (27, 5%); in comprehensive self-evaluation of abilities 155 students were located in Good for a 42,6 % and Very Good 168 for 46, 4 %. Conclusion: to acquire the adequate ability and trainig it is vital the sequential and repeted practice of several resuscitation maneuvers applying them to the manekins.